ENL mutation and AML: a new model that reveals oncogenic condensate's function in leukemogenesis - Zhong Fan; Yanan Jiang; Xiaotian Zhang (Molecular Oncology)
Precise regulation of gene expression is essential for proper development and the maintenance of homeostasis in organisms. Studies have shown that some transcriptional regulatory proteins influence gene expression through the formation of dynamic, locally concentrated assemblies known as condensates, while dysregulation of transcriptional condensates was associated with several cancers, such as Ewing sarcoma and AML [Wang Y et al. (2023) Nat Chem Biol 19, 1223–1234; Chandra B et al. (2022) Cancer Discov 12, 1152–1169]. Mutations in the histone acetylation “reader” eleven‐nineteen‐leukemia (ENL) have been shown to form discrete condensates at endogenous genomic targets, but it remains unclear how ENL mutations drive tumorigenesis and whether it is correlated with their condensate formation property. Liu et al. now show, using a conditional knock‐in mouse model, that ENL YEATS domain mutation is a bona fide oncogenic driver for AML. This mutant ENL forms condensates in hematopoietic stem/progenitor cells at the genomic loci of key leukemogenic genes, including Meis1 and Hoxa cluster genes, and disrupting condensate formation via mutagenesis impairs its chromatin and oncogenic function. Furthermore, they show that small‐molecule inhibition of the acetyl‐binding activity displaces ENL mutant condensates from oncogenic target loci, and this inhibitor significantly impairs the onset and progression of AML driven by mutant ENL in vivo.